Cardiac Specialists' Perspectives on Barriers to Cardiac Rehabilitation Referral and Participation in a Low-Resource Setting. (August 2020) - Ghanbari-Firoozabadi, Mahdieh; Mirzaei, Masoud; Nasiriani, Khadijeh; Hemati, Mozhgan; Entezari, Jamal; Vafaeinasab, Mohammadreza; Grace, Sherry L; Jafary, Hasan; Sadrbafghi, Seyed Mahmood
Background: Cardiac specialists are arguably the most influential providers in ensuring patients access cardiac rehabilitation (CR). Physician barriers to referral have been scantly investigated outside of high-income settings, and not qualitatively. Aim: This study investigated cardiac specialists' perceptions of barriers and facilitators to patient CR participation in a low-resource setting, with a focus on referral. Methods: In this qualitative study, focus groups were conducted with conventional content analysis. Thirteen of 14 eligible cardiac specialists working in Yazd, Iran, participated in 1 or both focus groups (n = 9 and n = 10, respectively). The recording of the first focus group was transcribed into a word file verbatim, and the accuracy of the content of all field notes and the transcripts was approved by the research team, which was then analyzed inductively. Following a similar process, saturation was achieved with the second focus group. Results: Four themes emerged: "physician factors, " "center factors, " "patient factors, " and "cultural factors." Regarding "physician factors, " most participants mentioned shortage of time. Regarding "center factors, " most participants mentioned poor physician-patient-center coordination. In "patient factors, " the subcategories that arose were socioeconomic challenges and clinical condition of the patients. "Cultural factors" related to lack of belief in behavioral/preventive medicine. Conclusions: Barriers to CR referral and participation were multilevel, as in high-resource settings. However, relative recency of the introduction of CR in these settings seemed to cause great lack of awareness. Cultural beliefs may differ, and communication from CR programs to referring providers was a particular challenge in this setting.